Morpho-physiological characterization of two wheat genotypes with contrasting trait of heat tolerance. - Bakshi, Suman; Jambhulkar, Sanjay J.; Agarwal, Rachna (Journal of Cereal Research, 2020)
Various biotic and abiotic stresses adversely affect crop yield across the globe. Wheat is cool-season cereal crop and sensitive to rise in ambient growth temperature. Ninety genotypes were screened under heat stress and non-heat stress locations. Low heat susceptibility index of <0.5 for HD2189, N5643, Kenphad39, HD2501, NI179, NI5439, HS240, HD2428 and HD2687 indicated that they are heat tolerant and high susceptibility index of >1.5 for PBN142, NI9947, HD2320, GW190, HD2135, NI917 and Batavia indicated that they are heat susceptible. Based on grain yield and heat susceptibility index, two genotypes namely HD2189 and Batavia with contrasting response to heat stress were selected for the further studies. Their morphological and physiological characterization was carried out at seedling stage using 22°C as control and 33°C as heat stress. Under heat stress conditions, reduction for seedling growth traits, relative water content (RWC) and membrane thermostability (MTS) was less in HD2189 (25.3%, 10.2%, 13%) compared to Batavia (55.3%, 34.4%, 30%). HD2189 maintained lower canopy temperature with depression values in the range of 3.75 to 8°C compared to Batavia (2.82 to 5.10°C). The conversion of source to sink was better for HD2189 as displayed by translocated dry matter (TDM), translocation efficiency (TE), contribution of plant assimilates (CPA), longer duration of grain filling, grain yield and yield components under high temperature. Trend for electron transport rate of PSII (ETRII) and effective quantum yield (YII) for both the varieties at 22°C and 33°C was similar. However, Batavia plants were adjusting through non-regulated heat dissipation indicating damage to the photosynthetic apparatus whereas HD2189 showed higher regulated heat dissipation. Thus, genotype HD2189 showed heat tolerance at seedling and adult plant stages compared to Batavia.